(untitled) (Journal of Human Sciences, 2021)
The idea of the research started from the clear difference between the extent of benefit from teaching Arabic grammar and its application in society, the predominance of colloquial dialects over classical Arabic, which often negatively affected the level of thinking and expression of some students. This effect reached a low level of understanding and making understand, which made linguistic errors common and widespread in the state’s facilities and official offices, read and written media and scientific (academic) theses, so This research was entitled: “Teaching the rules of the Arabic language between standard and descriptive”, and lies The importance of research in linking the rules of the language system (language competence), and the rules of using the language system (discourse competence). One of the most important objectives that the research seeks to reach is to clarify the close relationship between the rules of the language system, the use and the rules of the language system, and that use is the main goal of the language. Other reasons for choosing the topic is the blatant error (in reading and writing) in the use of Arabic grammar and in teaching its courses, and in the various sciences in schools, universities and scientific research. and various media. Among the most important questions that will be answered, what are the reasons for the low level of grammar comprehension? Is the defect in the curriculum or in the method? Or in both? Or in the teacher? In this research, the descriptive approach based on the analysis based on the extrapolation of the phenomenon will be followed, and then describing it for conformity, issuing judgments and generalizing them, and the research was divided into the following sections: 1. Introducing the language system, and the rules for its use, the language system. 2. The relationship between the language system and the rules of its use. 3. The role of the Arabic language teacher in the process of linking the language system and the rules of its use 4. How to employ the curriculum in linking the language system and the rules of its use